An Exploratory Study of "Fake News" and Media Trust in Kenya, Nigeria and South Africa. Issue 1 (2nd January 2019) - Wasserman, Herman; Madrid-Morales, Dani
ABSTRACT: In recent years, concerns about the perceived increase in the amount of "fake news" have become prevalent in discussions about media and politics, particularly in the United States and Europe. However, debates around "fake news", even if some object to the use of the term due to it being loosely defined, appear to speak of processes that occur not only in the Global North but also elsewhere. In Africa, mis- and disinformation campaigns have been used to influence political agendas, and governments have responded with countermeasures. This article explores the phenomenon in Kenya, Nigeria and South Africa using data from a two-wave online survey ( N = 1847). We find that perceived exposure to disinformation is high, and that trust in social and national media is low. We also identify a significant relationship between higher levels of perceived exposure to disinformation and lower levels of media trust in South Africa. The limitations of this study, which focuses on a subset of the population that is highly educated, the implications of our findings, and recommendations for future research are discussed.